ANALISIS PENGARUH PERJANJIAN UTANG, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA RIIL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setiawati, Loh Wenny; Lieany, Lieany (Universitas Katolik Indonesia Atma Jaya, 2016)
Real Earnings Management is the real operating management activities undertaken by  manager for a particular purpose.  Real earnings management directly affect the cash flows of current and future, also the amount of accrual accounting, making it difficult to be monitored and detected by the board, auditors, regulators, and other stakeholders, as well as difficult for investors to be understood.  Therefore, companies management prefer to do real earnings management, compared to rely on accrual earnings manipulation. This research aims to determine the effect of the debt covenant, institutional ownership, and firm size to real earnings management. This research uses the method of multiple linear regression analysis, using data from the Indonesia Stock Exchange with samples of 156 companies for the period 2012 - 2014. Empirically, it was found that the debt covenant was not affected to the real earnings management, while institutional ownership and firm size were affected to the real earnings management.